Magnetic Lignosulfonate-Supported Pd Complex: Renewable Resource-Derived Catalyst for Aqueous Suzuki-Miyaura Reaction - Nasrollahzadeh, Mahmoud; Issaabadi, Zahra; Varma, Rajender S (ACS omega, 2019)
A novel strategy is described to prepare magnetic Pd nanocatalyst by conjugating lignin with Fe3O4 nanoparticles via activation of calcium lignosulfonate, followed by combination with Fe3O4 nanoparticles. Tethering 5-amino-1H-tetrazole to calcium lignosulfonate-magnetite hybrid through 3-chloropropyl triethoxysilane enabled coordination of Pd salt with Fe3O4-lignosulfonate@5-amino-1H-tetrazole. The underlying changes of the lignosulfonate are identified, and the structural morphology of attained Fe3O4-lignosulfonate@5-amino-1H-tetrazole-Pd(II) (FLA-Pd) is characterized by Fourier transform infrared, thermogravimetry differential thermal analysis, energy-dispersive spectrometry, field-emission scanning electron microscopy, transmission electron microscopy, and vibrating sample magnetometer (VSM). The synthesized FLA-Pd displayed high activity for phosphine-free C(sp2)-C(sp2) coupling in water, and the catalyst could be reused for seven successive cycles.